The 2020 earthquake sequence and seismic hazard scenario of Mizoram state in northeast India - Bansal, Brijesh K.; Sutar, Anup K.; Verma, Mithila (Frontiers in Earth Science, 2022)
The Mizoram state of India lies in close proximity to the active Indo-Burma subduction zone and experiences moderate to large earthquakes, including the M7 event in 1938. Since 2015, only 2 events with 5